The effect of naphthylamine compounds on GSH-Px activity in the hemolymph of fluoride poisoned silkworm larvae - LÜ Shun-lin; GU Guo-da; DING Chun-yang (浙江大学学报. 农业与生命科学版, 2000)
In order to understand the mechanism of the detoxication of the fluoride poisoned silkworm by naphthy-lamine compounds such as CRL, the effect of CRL on the activity of the glutathione peroxidase (GSH-Px) in the hemolymph of fluoride poisoned silkworm larvae was studied. For normal fifth instar larva, the GSH-Px activity was relatively higher in the middle of the stage, while it was lower both in the beginning and the end of the stage. After feeding 15 mmol/L of NaF solution, the GSH-Px activity increased obviously, however, it decreased with the treatment of CRL, and it became much lower with the treatment of CRL and the synergist together.